2018
DOI: 10.1002/acm2.12349
|View full text |Cite
|
Sign up to set email alerts
|

TG‐51 reference dosimetry for the Halcyon™: A clinical experience

Abstract: Halcyon™ is a single‐energy (6 MV‐FFF), bore‐enclosed linear accelerator. Patient setup is performed by first aligning to external lasers mounted to the front of the bore, and then loading to isocenter through pre‐defined couch shifts. There is no light field, optical distance indicator or front pointer mechanism, so positioning is verified through MV imaging with kV imaging scheduled to become available in the future. TG‐51 reference dosimetry was successfully performed for Halcyon™ in this imaging‐based setu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 7 publications
2
44
0
Order By: Relevance
“…The beam quality was recorded following TG‐51 guidelines as % dd (10) . The beam was not filtered with lead for these measurements however Lloyd et al has shown this to impact the measured % dd (10) by less than 0.7% on the Halcyon . This ranged from 59.85% for a 5 cm square field to 68.5% for 28 cm square field.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beam quality was recorded following TG‐51 guidelines as % dd (10) . The beam was not filtered with lead for these measurements however Lloyd et al has shown this to impact the measured % dd (10) by less than 0.7% on the Halcyon . This ranged from 59.85% for a 5 cm square field to 68.5% for 28 cm square field.…”
Section: Resultsmentioning
confidence: 99%
“…18 The beam was not filtered with lead for these measurements however Lloyd et al has shown this to impact the measured %dd(10) by less than 0.7% on the Halcyon. 19 This ranged from 59.85% for a 5 cm square field to 68.5% for 28 cm square field. For all distances past dmax, the measured data agreed with the TPS data to within 1% for all field sizes.…”
Section: A Dosimetric Parametersmentioning
confidence: 96%
“…Halcyon plans: The Halcyon is a ring-based delivery system [13,[22][23][24]. It consists of a linear accelerator capable of producing a 6MV flattening filter-free (FFF) photon beam delivering (when calibrated to deliver 1.0Gy per 100 monitor units (MU) at the reference conditions of source-surface distance (SSD) 100 cm at d max depth of 1.3 cm) a maximum dose rate of 800MU/min.…”
Section: The Treatment Planning Techniques and Featuresmentioning
confidence: 99%
“…There are a number of publications that either evaluate the operation of the Halcyon or provide recommendations on its clinical use . A recent publication provided a risk assessment of Halcyon acceptance testing and commissioning processes using the TG‐100 methodology .…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of publications that either evaluate the operation of the Halcyon or provide recommendations on its clinical use. [1][2][3][4][5][6][7][8][9][10][11] A recent publication provided a risk assessment of Halcyon acceptance testing and commissioning processes using the TG-100 methodology. 12 In that work, 142 failure modes were identified with the top risk priority number (RPN) values ranging from 85.5 to 95.0 for the acceptance testing and commissioning, respectively.…”
Section: Introductionmentioning
confidence: 99%